Edição gênica por CRISPR/CAS9: uma estratégia de ensino das biotecnologias com ênfase na bioética - Mara Letícia Carvalho de Souza Martins (2022)
The present work is a research whose product is a didactic sequence anchored in the CTSA (Science, Technology, Society and Environment) movement and with an investigative bias in a proposal to develop student protagonism and promote citizen training. We use the gene editing biotechnology known as CRISPR, which stands for Clustered Regularly Interspaced Short Palindromic Repeats, as a means for teaching and discussing concepts related to genetics and molecular biology in the light of bioethics. Gene editing and its biotechnologies are polemical and controversial topics that have great potential for effective learning in Biology and fostering citizen education. The CRISPR technique is not well- known in different spheres of society and not present is most high school textbooks. In the sequence developed, we used: 1) a questionnaire to verify previous knowledge about genetics and molecular biology and to enable the discussion of concepts allowing the construction of knowledge in a group; 2) case studies with situations involving gene editing in humans and that were intended to stimulate the discussion on CRISPR in a critical way; 3) artistic representation of a popular jury prepared by the students themselves on the presented biotechnology. The sequence was developed with students from the 1st grade of a state public school in Minas Gerais in the discipline Natural Sciences and its Technologies in the newly implemented new high school. Analyzes of the previous knowledge questionnaire were carried out, which revealed that the students had difficulty in establishing a relationship between the concepts of gene, chromosome and DNA. However, the classroom discussions led them to build knowledge collectively in order to recognize the error and understand the correct answer. Responses on the proposed case studies were analyzed and categorized according to content analysis methodology. It was evident that there is no consensus on the manipulation of human DNA and that the students did not know about gene editing biotechnologies, but listed a greater number of positive than negative consequences on the technique, establishing criteria for its use in society. The mock jury proved to be an effective tool for teaching gene editing tools from a bioethical perspective. It is believed that the present work can help teachers to stimulate critical thinking and student protagonism.